Perencanaan Kawasan Pariwisata Pantai yang Berkelanjutan - Muh Adhim Arasy; Slamet Trisutomo; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Takalar District, which is an area that has a variety of potential as the allotment of tourist areas, especially coastal areas. One of the coastal tourism objects that has the potential to be developed is Gusunga Beach, which is located in Bontosunggu Village, North Galesong District. Based on the Regional Regulation of Takalar District No. 6 of 2012 concerning the Takalar District Spatial Plan for 2012-2031 states that Gusunga Beach is one of the nature tourism. The potential of Gusunga Beach can be assessed from the activities and culture of the surrounding community and the beauty of its natural panorama. However, the problem that have occurred is that Gusunga Beach has no management either from the government or the private sector, so that currently the management is carried out by the village authorities. This will have an impact on the tourism industry to the environment, economy and social. Based on the previous explanation, this study aims to develop the potential and tourist attraction of Gusunga Beach as sustainable tourism using two methods, which are methods for analysis and methods for planning with a qualitative and quantitative approach. The analytical method is divided into four parts, which are sustainable tourism components, tourism components, tourist valuation, and infrastructure analysis. The planning method is divided into five parts, which are zoning plans for tourism area development, infrastructure planning, sustainable tourism strategy plans, development phasing plans, and development estimation plans.